Aberrant δPKC activation in the spinal cord of Wobbler mouse: a model of motor neuron disease - Kunjan R. Dave; Ami P. Raval; Jesús Purroy; Ilias G. Kirkinezos; Carlos T. Moraes; Walter G. Bradley; Miguel A. Pérez-Pinzón (Neurobiology of Disease, 2005)
Protein kinase C (PKC) was suggested to play a role in the pathology of amyotrophic lateral sclerosis (ALS) patients. Activation of PKC delta (δPKC) modulates mitochondrially induced apoptosis. The goal of the present study was to define whether δPKC activation occurs in Wobbler mouse spinal cord (a model of motor neuron disease). The level of δPKC in the soluble fraction was significantly decreased in the spinal cord of Wobbler mice, which was associated with a significant increase in δPKC cleavage. Since caspase-3 is known to cleave δPKC, we determined caspase-3 activation in the Wobbler mice spinal cord, immunohistochemically. The results demonstrated intense immunoreactivity for activated caspase-3 in corticospinal tract motor neurons of Wobbler mice spinal cord. We hypothesize from these results that caspase-3 activation cleaves δPKC, which in turn promotes an aberrant signal transduction pathway in the Wobbler spinal cord.